1993
DOI: 10.1177/001698629303700104
|View full text |Cite
|
Sign up to set email alerts
|

Creative Productivity Among Secondary School Students: Combining Energy, Interest, and Imagination

Abstract: This qualitative research study focuses upon 18 highly creative/productive secondary school students. Creative/ productive behavior is examined by studying characteristics of youths who pursued and completed investigations based on their interests. The data sources were the family, the school, and the student. Methods of investigation included document analysis, questionnaires, and a student interview. Reflecting on experiences in their respective programs for the gifted, students revealed insights into the wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
48
0
4

Year Published

1998
1998
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(52 citation statements)
references
References 17 publications
0
48
0
4
Order By: Relevance
“…Delcourt (1993) Creative productivity among secondary school students: Combining energy, interest, and imagination.…”
Section: Continuing Absence Of Challenge For Gifted and Talented Studmentioning
confidence: 99%
See 2 more Smart Citations
“…Delcourt (1993) Creative productivity among secondary school students: Combining energy, interest, and imagination.…”
Section: Continuing Absence Of Challenge For Gifted and Talented Studmentioning
confidence: 99%
“…Gifted education programs and strategies have been found to longitudinally benefit gifted and talented students, helping students increase aspirations for college and careers (Taylor, 1992), determine post-secondary and career plans (Delcourt, 1993;Hébert, 1993;Lubinski, Webb, Morelock, & Benbow, 2001;Taylor, 1992), develop creativity and motivation that was applied to later work (Delcourt, 1993;Hébert, 1993), and achieve more advanced degrees (Lubinski et al, 2001). Hébert (1993) and Delcourt (1993) found that gifted programs which were based on Renzulli's Triad/SEM approach (Renzulli, 1977;Renzulli & Reis, 1985 and focused on interest development and productivity in areas of interest, had a positive effect on students' subsequent interests, positively affected postsecondary plans; Reis (1985, 1997) also found that early advanced project work in gifted programs served as important training for later productivity.…”
Section: Longitudinal Benefits Of Gifted Education Programs and Pedagmentioning
confidence: 99%
See 1 more Smart Citation
“…Örneğin, aileler biyoloji proje çalışmalarında öğrencilerin kendilerini özgür, mutlu, heyecanlı, keyifli hissettiğini belirtmişlerdir. Bu sonuç, alan yazında yer alan öğrencilerin proje çalışmalarından hoşlandığı, proje çalışmalarının mutluluk verici, ilginç, eğlenceli, heyecanlı, zevkli ve tatmin edici olduğu (Baykoç, Uyaroğlu ve Aydemir, 2012;Delcourt, 1993;Johnsen, 2008; Johnsen ve Goree, 2009; Özarslan ve Çetin, 2012;Powers, 2008) Aileler öğrencilerin biyoloji proje çalışmalarının genelde başarılı olarak gerçekleştiğini ifade etmişlerdir. Bu sonuç, alan yazında yer alan, ailelerin proje çalışmalardan memnun olduğu bulgusu benzerlik göstermektedir (Baykoç vd., 2012).…”
Section: Tartişma Ve Sonuçunclassified
“…This four-stage approach gives emphasis on the unconscious rather than the conscious steps of creativity, while non-cognitive dimensions, such as motivation, energy, and commitment are emphasized (Delcourt, 1993).…”
mentioning
confidence: 99%